Immersive virtual reality for science learning: Design, implementation, and evaluation - Matovu, Henry; Ungu, Dewi Ayu Kencana; Won, Mihye; Tsai, C.C.; Treagust, David; Mocerino, Mauro; Tasker, R. (2022)
The advanced visualisation and interactive capabilities make immersive virtual reality (IVR) attractive for educators to investigate its educational benefits. This research reviewed 64 studies published in 2016–2020 to understand how science educators designed, implemented, and evaluated IVR-based learning. The immersive design features (sensory, actional, narrative, and social) originally suggested by Dede provided the framework for the analysis of IVR designs. Educators commonly adopted IVR to better aid visualisation of abstract concepts and enhance learning experience. IVR applications tended to have sensory and actional features, leaving out narrative and social features. Learning theories did not appear to play a strong role in the design, implementation, and evaluation of IVR-based learning. Participants generally reported their IVR experiences as positive on engagement and motivation but the learning outcomes were mixed. No particular immersive design features were identified to result in better learning outcomes. Careful consideration of the immersive design features in alignment with the rationales for adopting IVR and evaluation methods may contribute to more productive investigations of the educational benefits of IVR to improve science teaching and learning.